مهنة الصيد من خلال الرسومات المصرية - eali, sajad (Journal of College of Education, 2022)
Abstract The researcher dealt with the drawings of fishermen in the tombs of the nobles of all kinds, from land and sea fishermen, as well as their tools for fishing. The tools and the image of fishing differed according to the need for hunting, so the king’s hunting was for a picnic, then the fishing was done with the hook and the spears, as for the workers, they hunted to earn a livelihood and was done with nets to collect the largest amount of fish, so the work is the same, but the goal is different. Key words: wildlife hunting, fishing, hunting equipment